2022
DOI: 10.1590/1678-4162-12827
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and nutrient extraction by Paiaguás palisadegrass, single and intercropping with pigeon pea, submitted to doses of nitrogen

Abstract: The objective of this work was to evaluate the productivity and extraction of macronutrients by Urochloa brizantha cv. BRS Paiaguás (Syn. Brachiaria brizantha cv. BRS Paiaguás) single and intercropped with pigeon pea (Cajanus cajan cv. BRS Mandarim), subjected to four doses of nitrogen applied in topdressing (0, 80, 160 and 240 kg ha-1). The experiment was carried out in São Luís de Montes Belos, GO, in soil classified as dystrophic red latosol, under Cerrado conditions. Plant height and dry mass of pigeon pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…In the Brazilian cerrado (the same region as the present study), Rezende et al [39] observed that Paiaguás palisade grass, when intercropped with pigeon pea (as in the PPPG treatment), exhibited a higher concentration of minerals in its leaves compared to monoculture. Since legumes improve the chemical composition of soil by increasing its organic matter and nitrogen levels, they provide positive agronomic benefits for plants grown in intercropping systems with legumes [12][13][14].…”
Section: Fm and Chemical Composition Of The Silagesupporting
confidence: 60%
“…In the Brazilian cerrado (the same region as the present study), Rezende et al [39] observed that Paiaguás palisade grass, when intercropped with pigeon pea (as in the PPPG treatment), exhibited a higher concentration of minerals in its leaves compared to monoculture. Since legumes improve the chemical composition of soil by increasing its organic matter and nitrogen levels, they provide positive agronomic benefits for plants grown in intercropping systems with legumes [12][13][14].…”
Section: Fm and Chemical Composition Of The Silagesupporting
confidence: 60%
“…Las dosis crecientes de residuos líquidos (0 m³ ha -1 , 150 m³ ha -1 , 300 m³ ha -1 , 450 m³ ha -1 , 600 m³ ha -1 ) condujeron a un aumento significativo de las fracciones de N, P, Ca, Mg, S y Fe en las láminas foliares de pasto insurgente. De acuerdo con Tomazello et al (22) y Rezende et al (23) , el aporte adecuado de nutrientes mejora la acumulación de N, P, Ca, S y Mg en la parte aérea de las gramíneas tropicales manejadas en regiones de sabana. Además, mejora el valor nutricional del forraje producido.…”
Section: Contenido De Nutrientes En Las Láminas De Las Hojas Del Past...unclassified
“…To achieve high yields, the application of 80 kg ha -1 P 2 O 5 and 60 kg ha -1 K 2 O as fertilizers is recommended (Sousa & Lobato, 2004). However, purchasing chemical fertilizers can increase production costs (Rezende et al, 2022;Leal et al, 2023).…”
Section: Introductionmentioning
confidence: 99%